Developing Support Systems for Supporting Entrepreneurs and Small Business in Agrotechnology in Kluang, Johor : A Proposal Using the Cluster Based Approach - Chieng, Ngee Yew Clifford (2013)
The aim of this report is to conduct a study on a proposal to develop support systems for entrepreneurs and small businesses in agrotechnology (“Proposal”). The study of the Proposal will include the use of a cluster-based approach to evaluate and guide the planned development of three pieces of land (“Proposed Land”) with a total combined area of approximately 60 acres in the district of Kluang, Johor, Malaysia. This report will begin with an overview and an analysis of the agriculture sector in Malaysia and the issues it faced over the last decade. This is followed by a discussion on the future prospects of the Malaysian agriculture sector. This report then goes on to highlight and discuss some of the relevant literature and theories relevant to the study of the Proposal. Section 4 of this report will highlight research methods and objectives that outline the basis of which the research will be carried out.The research will begin in Section 5 of this report with an overview and analysis on the state of Johor, Malaysia and its district of Kluang and their contributions to the agriculture sector. Section 5 concludes with the mapping of the Kluang Agriculture Cluster. Section 6 and 7 of this report presents an overview and analysis of relevant governmental ministries, agencies and organisations as well as their policies, strategies, initiatives and incentives. An analysis and mapping of the Proposed Land is performed in Section 8 of this report to identify the geographical location of the Proposed Land, identify its surrounding areas. In Section 9 of this report, the Porter‟s Diamond model is used to analyse and compare the competitiveness of the Kluang agriculture sector in comparison to the Johor agriculture sector. Based on the research conducted, the development plan for the Proposal was constructed. Following a discussion on the development plan, potential future linkages were identified. This is followed by a discussion on the rationales for the proposal as well as its other benefits. In conclusion, the research objectives of this report were met.